Service quality in Medellin hotels using perceptual maps: Análisis de la calidad del servicio en hoteles de Medellín usando mapas perceptuales - Vanegas, Juan Gabriel; Restrepo, Jorge Anibal; Barros, Gilly Andrea; Agudelo Moreno, Gisella (Cuadernos de Administración, 2018)
The online comments and assessments made by hotel customers provide relevant information to determine the various dimensions of the service received. In this context, the purpose of this work is to evaluate the quality perceived by national and international guests staying at different hotels in Medellín (Colombia). To this end, the multidimensional scaling technique of perceptual maps was used to apply to 9,153 comments made on the TripAdvisor platform to 57 hotels between 2005 and 2010. The main finding shows that the factors most valued by guests are cleanliness, quality of rest and service above the location, price and comfort of the rooms, although these factors differ according to the characteristics of the visitor and the hotel.